If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 9 + -3 = 0 Reorder the terms: 9 + -3 + 3x = 0 Combine like terms: 9 + -3 = 6 6 + 3x = 0 Solving 6 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 0 + -6 3x = 0 + -6 Combine like terms: 0 + -6 = -6 3x = -6 Divide each side by '3'. x = -2 Simplifying x = -2
| 2.5d+3.25=1+3.25d | | 12y+72=11x+33 | | 4x+15=7x-2 | | 3r=5.22 | | 70-(2x+15)=3 | | 4-5(y+2)=-11y+9 | | 4x=(130-x)/3 | | y=tan(x) | | X+6=7x-24 | | 8=12-x/6 | | 10w=570 | | 5u+23=6u+-17 | | 5(3x+4)=80 | | -141=-9x-6 | | 2(x+3)+3(x-1)=-7 | | s-7=2/3s+7-3 | | -728=-8m | | .8m+2.7m+4.3=25.7 | | 2k-3=3 | | a=12-x/6 | | -6+9n=75 | | 42=6+3x | | 0.02(n-1)+0.6=2.4 | | -195=c+801 | | 6-2(x+3)= | | 5x+3=7x-17 | | 729=n^(3/2) | | -5z=-825 | | 2a^2-13a+21=0 | | 7x+9=25 | | 5x-4=x-10/3 | | X+44=90 |